The incidence and economic burden of injuries in Jiangxi, China. (September 2016) - Fang, X.; Zeng, G.; Linnan, H.W.; Jing, R.; Zhu, X.; Corso, P.; Liu, P.; Linnan, M.
Abstract: Objectives: This study estimated the incidence, direct medical and non-medical costs, and productivity losses due to morbidity and mortality across multiple strata for injuries that occurred in Jiangxi, China. Study design: Cross-sectional study. Methods: Data came from the Jiangxi injury survey, a provincially-representative, population-based sample of 100, 010 households. The major economic costs of injuries were divided into direct costs and indirect costs. Direct costs encompass medical costs and direct non-medical costs. Indirect costs refer to the productivity losses due to injury-related morbidity and mortality. Results: In 2005, about one of 18 residents in Jiangxi, China, experienced an injury. Overall, fall, animal bite, and road traffic crash (RTC) injuries accounted for more than 66% of all injuries, while fall, RTC, drowning, and self-harm injuries accounted for 80% of fatal injuries. Average cost per case for a fatal injury was 163, 389 RMB ($20, 171) for lost productivity and 2800 RMB ($346) in direct medical & non-medical costs. A non-fatal injury resulting in hospitalisation or permanent disability on average caused 5221 RMB ($643) in direct costs and 18, 437 RMB ($2276) in lost productivity and, an additional loss of three school days. A non-hospitalised non-fatal injury on average caused 303 ($37) RMB in direct costs and 491 RMB ($61) in lost productivity and, an additional loss of 0.5 school days. Conclusions: The unequivocal evidence of the substantial health and financial burden of injuries indicates to Chinese policy makers that more research and efforts are needed to find efficacious and cost-effective interventions targeting injury. Highlights: We estimate the incidence and economic burden of injuries in Jiangxi, China. Data came from one of the largest community based injury surveys ever conducted in a developing country. About one of 18 residents in Jiangxi experienced an injury in 2005. Fall, animal bite, and road traffic crash injuries accounted for more than 66% of all injuries. On average, each injury generated 7124 RMB ($880 US dollars) in direct and indirect costs.